A new approach for pulse amplitude measurement using Lagrange's interpolation for radiation or particle detectors. Issue 2 (15th January 2023) - Patel, Arpit; Mazumdar, Himanshu; Patel, Bhumi
Abstract: In radiation detector signal processing, usually, the charge-sensitive preamplifier converts the small charge signal coming from the semiconductor-based detector into voltage form and then the signal is further amplified to measure the energy of the incoming radiation. The voltage pulse from a charge-sensitive preamplifier (CSPA) is amplified using a shaping amplifier which reduces the signal bandwidth. To achieve better energy resolution, precise measurement of the peak amplitude of shaping amplifier output is required. The signal processing methods are available in which the signal from the charge-sensitive preamplifier can be directly digitized using high-speed Analog to Digital Converters (ADC), and then further signal processing such as gain and shaping is carried out inside the Field Programmable Gate Arrays (FPGA). For multiple detector systems, digital signal processing methods are quite difficult to implement in Field Programmable Gate Arrays (FPGA). In this context, The development of an alternative technique is initiated that uses a charge-sensitive preamplifier, shaping amplifier, low sampling analog-to-digital converter, and FPGA, where LaGrange's interpolation technique is implemented in FPGA to precisely measure the peak of the analog pulse. In this paper, the comparison of the proposed method with other pulse amplitude measurement techniques is discussed. Results show that the implemented technique gives similar energy resolution compared to digital pulse processing and standard peak detector-based techniques.